10.1016/s0029-7437(10)70403-1 (CrossRef Listing of Deleted DOIs, 2000)
Electrosurgical energy may facilitate difficult septal lead advancement during left bundle branch area pacing (LBBAP), but procedural feedback after each application is poorly defined. A 63-year-old woman with complete atrioventricular block had persistent left ventricular septal pacing (LVSP) despite deep septal engagement and prolonged mechanical rotation. Two brief 20-W AUTO CUT cycles were delivered through a stylet-driven pacing lead. The first was followed by no meaningful COI or mechanical change. The second was followed by a decrease in COI and renewed lead advancement. Output decrement subsequently demonstrated transition from nonselective to selective LBB capture, with S-V separation of 25 ms and shortening of V6 R-wave peak time from 90 to 73 ms.One-month imaging and electrical parameters remained stable.